Comparision of antibiotics on growth performance of weanling pigs in a commerical environment - Keegan, T.P.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 320 weanling pigs (10.7 lb and 14 ± 3 d of age, PIC) was used to determine the effects of antibiotics and an antibiotic alternative on nursery pig performance. Pigs were fed one of 5 experimental diets: 1) control with no antimicrobials; 2) carbadox (50 g/ton); 3) Denagard/CTC (35 g/ton Denagard™, 400 g/ton Chlortetracycline); 4) Neo-Terramycin® (140 g/ton Neomycin Sulfate, 140 g/ton Oxytetracycline HCl); 5) Bio Mos (0.3%, mannanoligosaccharide). Overall (d 0 to 31 post-weaning), pigs fed the diet containing Denagard/CTC had the greatest (P<0.05) ADG and ADFI compared to pigs fed all other treatment diets. Pigs fed the diet containing Neo-Terramycin had greater (P<0.05) ADG compared to pigs fed the control diet or diets containing Carbadox or Bio Mos. In addition, pigs fed the diet containing Neo-Terramycin had greater (P<0.05) ADFI compared to pigs fed the control diet or the diet containing Bio Mos. In conclusion, the addition of carbadox and Bio Mos did not result in improved growth performance compared to pigs fed the control diet. However, improvements were seen in average daily gain and daily feed intake with the addition of Denagard/CTC and Neo-Terramycin. Commercial operations need to determine which feed additives improve nursery pig performance in their individual production systems.
Keywords: Nursery pig; Antibiotics; Feed Additive; Swine